A Case Report of Progressive Brown Syndrome?. (10th May 2018) - Coughlan, A.; Arblaster, G. E.; Burke, J. P.
Aim: To report an unusual case of progressive Brown syndrome and the successful surgical treatment. Methods: A 42-year-old male with a documented 14-year history of progressive Brown syndrome is presented. To improve diplopia symptoms an ipsilateral superior oblique (SO) 7 mm silicone tendon spacer and a contralateral 3 mm superior rectus (SR) recession were performed. Results: The surgical procedure was successful in reducing the primary position deviation (preoperative 30ΔLHoT 7ΔLXT; one month post surgery 3ΔLHo; one year post surgery 7-8ΔLHo 1-2ΔE) and eliminating the abnormal head posture (AHP). Diplopia was only reported on elevation and depression following surgery. Conclusion: This case of Brown syndrome is unusual as it was progressive and had a documented history over a number of years prior to surgery. Surgical treatment of Brown syndrome is rarely required, but in this case was successful in improving the patient's diplopia and AHP.